Evolution of lung function during the first year of life in newborn screened cystic fibrosis infants. Issue 10 (26th September 2013) - Nguyen, The Thanh-Diem; Thia, Lena P; Hoo, Ah-Fong; Bush, Andrew; Aurora, Paul; Wade, Angie; Chudleigh, Jane; Lum, Sooky; Stocks, Janet
Abstract : Rationale: Newborn screening (NBS) for cystic fibrosis (CF) allows early intervention. Design of randomised controlled trials (RCT) is currently impeded by uncertainty regarding evolution of lung function, an important trial end point in such infants. Objective: To assess changes in pulmonary function during the first year of life in CF NBS infants. Methods: Observational longitudinal study. CF NBS infants and healthy controls were recruited between 2009 and 2011. Lung Clearance Index (LCI), plethysmographic lung volume (plethysmographic functional residual capacity (FRCpleth )) and forced expired volume (FEV0.5 ) were measured at 3 months and 1 year of age. Main results: Paired measurements were obtained from 72 CF infants and 44 controls. At 3 months, CF infants had significantly worse lung function for all tests. FEV0.5 improved significantly (0.59 (95% CI 0.18 to 0.99) z-scores; p<0.01) in CF infants between 3 months and 1 year, and by 1 year, FEV0.5 was only 0.52 (0.89 to 0.15) z-scores less than in controls. LCI and FRCpleth remained stable throughout the first year of life, being on average 0.8 z-scores higher in infants with CF. Pulmonary function at 1 year was predicted by that at 3 months. Among the 45 CF infants with entirely normal LCI and FEV0.5 at 3 months, 80% remained so at 1 year, while 74% of those with early abnormalities remained abnormal at 1 year. Conclusions: This is the first study reporting improvements in FEV0.5 over time in stable NBS CF infants treated with standard therapy. Milder changes in lung function occurred by 1 year than previously reported. Lung function at 3 months predicts a high-risk group, who should be considered for intensification of treatment and enrolment into RCTs.